VNA in MF, HF and VHF bands - Brian Maximiliano Gluzman; Ramiro Avalos Ribas; Alejandro José Uriz; Juan Alberto Etcheverry; Leonardo David Vazquez; Jorge Castiñeira Moreira (Revista Elektrón)
This paper proposes the design and implementation of a vector network analyzer for frequencies up to 300 MHz. The device has the ability to measure the amplitude ratio and phase difference of the reflected and transmitted signal of a system under test with respect to an incident signal. The device generates a frequency sweep of square signals from 1 MHz to 100 MHz. The signal reflected by the system under test is separated from the incident signal by means of a Wheatstone bridge. The three signals are frequency converted and acquired by means of an audio codec with USB interface, and then processed in a computer to calculate the impedance, the S11 and S21 parameters. With the appropriate adjustment, it is possible to take advantage of the third harmonic synthesized by the generator and expand the measurement range up to 300 MHz.